Leituras do livro infantil ilustrado: a mediação inerente a livros premiados pela FNLIJ na categoria Criança - Tatyane Andrade Almeida (2016)
This research falls into the education and language field, and its intent is to explicit the mediation conditions intrinsic to the illustrated book. The corpus of analysis consists on literary works awarded by the National foundation of childrens and youth books FNLIJ on childrens category. It bases on the studies about childrens literature and, more specifically, about the picturebook, represented by the researchers Belmiro (2008, 2010, 2012, 2015), Oliveira (2008a, 2008b, 2012), Nikolajeva e Scott (2011), Salisbury e Styles (2013), Noldeman (1988), Beckett (2012) and Linden (2011). It utilizes concepts of literary theory and social semiotics, such as intertextuality, multimodality, style and metafiction, besides categories based on thematic definitions and literary genre - constructs of the contemporary production of literary works for childhood, which guides the analysis. We assume that the childrens picturebook establishes itself as a complex work in which the reading and signification process crosses different dimensions: material, verbal and visual. The highlighted categories, in turn, evidence the way that such dimensions have been used by writers and illustrators, and how the resultant effects promote changes on the mediation possibilities of the contemporary illustrated books. On these terms, the mediation of reading, understood as a large process of readers development, must be based on the understanding of the literary work as a whole, not by isolated aspects, such as practices of mediated readings which suppress a careful analysis of the illustration, the materiality of the book and the paratextual information. It was observed a fluidity of concepts on the Children category, among the diversity of the awarded books, and the childrens picturebook has been establishing itself in continuous dialogue with different medias and fields of cultural production, which amplifies the possibilities of signification - not only of the literary works studied, but also of larger artistic and cultural contexts, encouraging the development of more qualified readers since childhood.